Analisis Pemahaman Konsep Siswa Kelas 4 pada Materi Bilangan Bulat di Sekolah Dasar - Unaenah, Een; Safitri, Laura Amalya; Julianis, Tania (YASIN, 2023)
This study examined how well fourth-grade children understood the concepts related to the integer material taught to elementary school students. A descriptive study employing a concept understanding test instrument was used as the research methodology. Three pupils in grade 4 mad e up the study sample. Data was gathered using a written test that was given to the pupils and covered basic school-level topics on integers. The analysis's findings indicate that many pupils struggle to comprehend the idea of integers, particularly the concepts of positive and negative numbers as well as integer multiplication and division operations. Ineffective teaching strategies, a lack of practice, and individual student characteristics like curiosity and willingness to study are all factors that hinder student comprehension. In order to improve students' comprehension of integer concepts, teachers can devise engaging, engaging, and active learning strategies. They can also provide students with more intensive practice and enrichment of pertinent material, pay attention to individual student factors, and promote positive learning interest and motivation. This study offers guidance to primary school instructors and administrators on how to improve their students' comprehension of integer concepts. Additionally, this study can serve as a springboard for future studies aimed at creating more efficient learning methods for complicated mathematical materials.